2013
DOI: 10.1542/peds.2013-1193
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Therapy for Anxiety in Children With High-Functioning Autism: A Meta-analysis

Abstract: BACKGROUND: Anxiety is a common and impairing problem in children and adolescents with autism spectrum disorder (ASD). There is emerging evidence that cognitive-behavioral therapy (CBT) could reduce anxiety in children with high-functioning ASD.OBJECTIVE: To systematically review the evidence of using CBT to treat anxiety in children and adolescents with ASD. Methods for this review were registered with PROSPERO (CRD42012002722). METHODS:We included randomized controlled trials published in English in peer-rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
130
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(141 citation statements)
references
References 73 publications
9
130
0
2
Order By: Relevance
“…A recent systematic review and meta-analysis of this subject by Sukhodolsky et al (2013) identified eight randomised controlled trials, with sample sizes ranging from 22-71. These authors highlighted the form of control conditions for these studies, reporting that five studies used waitlist, two used treatment as usual and one an attentional control (that is; one that controls for clinician time and attention by also providing this in for the control group).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review and meta-analysis of this subject by Sukhodolsky et al (2013) identified eight randomised controlled trials, with sample sizes ranging from 22-71. These authors highlighted the form of control conditions for these studies, reporting that five studies used waitlist, two used treatment as usual and one an attentional control (that is; one that controls for clinician time and attention by also providing this in for the control group).…”
Section: Discussionmentioning
confidence: 99%
“…However, as we were comparing CBT against counselling (as opposed to more typical comparisons of therapy versus treatment as usual or waiting list) we wished to apply a more stringent fidelity test to ensure that none of the counselling therapists were using CBT techniques. Comparison of CBT against counselling, or of two types of psychotherapy with each other is rarely conducted, despite calls for this type of comparison (e.g., Sukhodolsky et al 2013). An extensive literature search identified only one fidelity measure designed specifically to compare CBT and counselling in either adults or children; the PCTPRS.…”
Section: Introductionmentioning
confidence: 99%
“…One of the ways to help autistic children or adolescent in recognizing complex emotion, such as disgust, would be to add Journal of Educational, Health andCommunity Psychology Vol 7, No 1, 2018 E-ISSN 2460-8467 Mammad Khaoula, Ahmed Ahami 30 sensations of smell and taste (Figure 1,2,3,4,&5). A recent study reported that children and adolescents with ASD are characterized by a relatively decreased modulation of amygdala activation when they consciously decrease affective responses to pictures that elicit disgust (Danial&Wood, 2013;Sukhodolsky et al, 2013). That study also found group differences in insula activation, potentially due to the use of more emotionally evocative disgust pictures compared to neutral faces (Pitskel et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…Psychosocial management includes the following interventions: behavioral parent training (BPT), adolescent-parent training in solving problems, training teachers to manage kids with ADHD and also all the three interventions mentioned above combined [15]. CBT may be also used for treating: anxiety [16], autism [17], and for children exposed to violence [18].…”
Section: Introductionmentioning
confidence: 99%